Recovery of (Z)-13-Docosenamide from IndustrialWastewater and Its Application in the Production of Virgin Polypropylene to Improve the Coefficient of Friction in Film Type Applications (2023)
Abstract: Additives play an important role in the production of plastic materials through their application, in which the mechanical, thermal, and physical properties of polymers are improved, making them last longer and be more resistant. During the synthesis of polypropylene resins, the remains of additives that are not absorbed by the resin are removed in the purification stage and end up in the wastewater. In this article, the recovery of (Z)-13-docosenamide from the wastewater from the process, its purification, and its application in the process was carried out. For the extraction of the additive, solid phase extraction (SPE) was used, and to guarantee the purity of (Z)-13-docosenamide, techniques such as high performance liquid chromatography (HPLC), Fourier transform infrared (FTIR), gas chromatography-mass spectrometry (GC/MS), thermogravimetric (TG) coupled with a gas chromatography-mass spectrometry (GC/MS), and differential scanning calorimetry (DSC) were used. The recovered erucamide was added to the PP between 0.05 and 0.3% w/w. The effects of the properties of the virgin polypropylene with the recovered additive were also evaluated to determine its effectiveness in improving the properties of the material by measuring the coefficient of friction (CoF) as well as the mechanical properties and wettability through atomic force microscopy (AFM) and the contact angle, respectively. It was discovered that using these techniques, it is possible to recover approximately 95% of the additive present in the water while keeping the material’s properties within the desired limits.